Cauchy-Schwarz inequality for inner product spaces

This page is a stub, so it contains little or minimal information and is on a to-do list for being expanded.The message provided is:
Flesh out statement

[ilmath]\newcommand{\ip}[2][]{\langle {#2} \rangle {#1} } [/ilmath]

Statement

Let [ilmath]\langle\cdot,\cdot\rangle:X\times X\rightarrow\mathbb{K} [/ilmath] be an inner product so [ilmath](X,\langle\cdot,\cdot\rangle)[/ilmath] is an inner product space, then[1]:

• [ilmath]\forall x,y\in X\left[\vert\ip{x,y}\vert\le\sqrt{\ip{x,x} }\sqrt{\ip{y,y} }\right][/ilmath]

Proof

• Let [ilmath]x,y\in X[/ilmath] be given
• We have two cases now, [ilmath]y\eq 0[/ilmath] and [ilmath]y\neq 0[/ilmath]
1. [ilmath]y\eq 0[/ilmath] case
• We now have two more cases, [ilmath]x\eq 0[/ilmath] and [ilmath]x\neq 0[/ilmath]
1. [ilmath]x\eq 0[/ilmath]
• Now [ilmath]\ip{x,y}\eq 0[/ilmath], [ilmath]\ip{x,x}\eq 0[/ilmath] and [ilmath]\ip{y,y}\eq 0[/ilmath] so:
• [ilmath]\vert\ip{x,y}\vert\eq 0\le\sqrt{\ip{x,x} }\sqrt{\ip{y,y} }\eq 0\times 0\eq 0[/ilmath] is the case
• [ilmath]0\le 0[/ilmath] obviously holds. We're done in this case
2. [ilmath]x\neq 0[/ilmath]
• Now [ilmath]\ip{x,y}:\eq\ip{x,0}\eq\overline{\ip{0,x} }\eq \overline{0\ip{z,x} } [/ilmath] for any [ilmath]z\in X[/ilmath]
[ilmath]\eq 0\ip{x,z}\eq 0[/ilmath]
• Now [ilmath]\vert\ip{x,y}\vert\eq 0[/ilmath] and [ilmath]\sqrt{\ip{x,x} }\sqrt{\ip{y,y} }\eq 0\sqrt{\ip{x,x} }\eq 0 [/ilmath] - as [ilmath]y\eq 0[/ilmath] [ilmath]\ip{y,y}\eq 0[/ilmath]
• [ilmath]\vert\ip{x,y}\vert\eq 0\le \sqrt{\ip{x,x} }\sqrt{\ip{y,y} }\eq 0[/ilmath] gives us [ilmath]0\le 0[/ilmath] which is obviously true (we have equality so we have [ilmath]\le[/ilmath])
2. [ilmath]y\neq 0[/ilmath] case
• Consider [ilmath]\lambda\in\mathbb{K} [/ilmath] then:
• [ilmath]0\le\ip{x-\lambda y,x-\lambda y} [/ilmath] (as for an inner product [ilmath]\forall z\in X[\ip{z,z}\in\mathbb{R}\wedge\ip{z,z}\ge 0][/ilmath]
• Then [ilmath]\ip{x-\lambda y,x-\lambda y}\eq \ip{x,x-\lambda y}-\lambda\ip{y,x-\lambda y} [/ilmath]
[ilmath]\eq\overline{\ip{x-\lambda y,x} }-\lambda\big(\overline{\ip{x-\lambda y,y} }\big)[/ilmath]
[ilmath]\eq\overline{\ip{x,x}-\lambda\ip{y,x} }-\lambda\big(\overline{\ip{x,y} - \lambda\ip{y,y} }\big) [/ilmath]
[ilmath]\eq\ip{x,x}-\overline{\lambda\ip{y,x} }-\lambda\ip{y,x} + \lambda\overline{\lambda}\ip{y,y} [/ilmath]
[ilmath]\eq\ip{x,x}-\overline{\lambda\ip{y,x} }-\lambda\ip{y,x} + \vert\lambda\vert^2\ip{y,y} [/ilmath][Note 1]
[ilmath]\eq\ip{x,x}-\big(\overline{\lambda\ip{y,x} }+\lambda\ip{y,x}\big)+\vert\lambda\vert^2\ip{y,y} [/ilmath][Note 2]
[ilmath]\eq\ip{x,x}-2\text{Re}(\lambda\ip{y,x})+\vert\lambda\vert^2\ip{y,y} [/ilmath]
[ilmath]\eq\left(\sqrt{\ip{x,x} }-\vert\lambda\vert\sqrt{\ip{y,y } }\right)^2-2\text{Re}(\lambda\ip{y,x})+2\vert\lambda\vert\sqrt{\ip{x,x} }\sqrt{\ip{y,y} } [/ilmath] - by completing the square
TODO: I think
(without considering the [ilmath]-2\text{Re}...[/ilmath])
• So [ilmath]\ip{x-\lambda y,x-\lambda y}\eq\left(\sqrt{\ip{x,x} }-\vert\lambda\vert\sqrt{\ip{y,y} }\right)^2-2\text{Re}(\lambda\ip{y,x})+2\vert\lambda\vert\sqrt{\ip{x,x} }\sqrt{\ip{y,y} } [/ilmath]
• Note that [ilmath]\forall z\in X[\ip{z,z}\ge 0[/ilmath] holds, so:
• [ilmath]0\le\ip{x-\lambda y,x-\lambda y}\eq\left(\sqrt{\ip{x,x} }-\vert\lambda\vert\sqrt{\ip{y,y} }\right)^2-2\text{Re}(\lambda\ip{y,x})+2\vert\lambda\vert\sqrt{\ip{x,x} }\sqrt{\ip{y,y} } [/ilmath]
• Or just [ilmath]0\le\left(\sqrt{\ip{x,x} }-\vert\lambda\vert\sqrt{\ip{y,y} }\right)^2-2\text{Re}(\lambda\ip{y,x})+2\vert\lambda\vert\sqrt{\ip{x,x} }\sqrt{\ip{y,y} } [/ilmath]
• Define [ilmath]\theta\in[0,2\pi) [/ilmath] such that [ilmath]\ip{y,x}\eq\vert\ip{y,x}\vert e^{j\theta} [/ilmath] (a form of complex number)
• Define $\lambda:\eq\frac{\sqrt{\ip{x,x} } }{\sqrt{\ip{y,y} } } e^{-j\theta}$ and note that $\vert\lambda\vert\eq\frac{\sqrt{\ip{x,x} } }{\sqrt{\ip{y,y} } }$
• this is fine to do as [ilmath]y\neq 0[/ilmath] so [ilmath]\ip{y,y}>0[/ilmath] so [ilmath]\sqrt{\ip{y,y} }>0[/ilmath] and the division in the fraction is defined
• we substitute this into our expression to obtain:
• $0\le\left(\sqrt{\ip{x,x} }-\frac{\sqrt{\ip{x,x} } }{\sqrt{\ip{y,y} } }\sqrt{\ip{y,y} }\right)^2-2\text{Re}\left(\frac{\sqrt{\ip{x,x} } }{\sqrt{\ip{y,y} } } e^{-j\theta}\ip{y,x}\right)+2\frac{\sqrt{\ip{x,x} } }{\sqrt{\ip{y,y} } }\sqrt{\ip{x,x} }\sqrt{\ip{y,y} }$
$\implies 0\le\underbrace{\left(\sqrt{\ip{x,x} }-\sqrt{\ip{x,x} }\right)^2}_{\eq 0}-2\text{Re}\left(\frac{\sqrt{\ip{x,x} } }{\sqrt{\ip{y,y} } } e^{-j\theta}\vert\ip{y,x}\vert e^{j\theta}\right)+2\frac{\sqrt{\ip{x,x} } }{\sqrt{\ip{y,y} } }\sqrt{\ip{x,x} }\sqrt{\ip{y,y} }$
$\implies 0\le -2\text{Re}\left(\frac{\sqrt{\ip{x,x} } }{\sqrt{\ip{y,y} } }\vert\ip{y,x}\vert e^0\right)+2\ip{x,x}$ - but [ilmath]e^0\eq 1[/ilmath][Note 3] so there is no imaginary component of the thing in the [ilmath]\text{Re} [/ilmath]
$\implies 0\le 2\ip{x,x}-2\vert\ip{y,x}\vert\frac{\sqrt{\ip{x,x} } }{\sqrt{\ip{y,y} } }$
$\implies 2\vert\ip{y,x}\vert\frac{\sqrt{\ip{x,x} } }{\sqrt{\ip{y,y} } }\le 2\ip{x,x}$ $\implies\vert\ip{y,x}\vert\frac{\sqrt{\ip{x,x} } }{\sqrt{\ip{y,y} } }\le \ip{x,x}$
[ilmath]\implies\vert{\ip{y,x} }\vert\sqrt{\ip{x,x} }\le \ip{x,x}\sqrt{\ip{y,y} } [/ilmath]
• [ilmath]\implies\vert\ip{y,x}\vert\le\sqrt{\ip{x,x} }\sqrt{\ip{y,y} } [/ilmath] - almost as required
• Note that [ilmath]\vert\ip{x,y}\vert\eq\vert\overline{\ip{x,y} }\vert\eq\vert\ip{y,x}\vert [/ilmath][Note 4]
• So [ilmath]\vert\ip{x,y}\vert\eq\vert\ip{y,x}\vert\le\sqrt{\ip{x,x} }\sqrt{\ip{y,y} } [/ilmath]
• Thus [ilmath]\vert\ip{x,y}\vert\le \sqrt{\ip{x,x} }\sqrt{\ip{y,y} } [/ilmath] - as required
• Since [ilmath]x,y\in X[/ilmath] were arbitrary we have shown the claim holds for all.

This completes the proof.

Notes

1. Let [ilmath]a+bj\in\mathbb{C} [/ilmath], then:
• [ilmath](a+bj)\overline{(a+bj)}\eq(a+bj)(a-bj) [/ilmath]
[ilmath]\eq a^2-j^2b^j +j(ab-ab)[/ilmath]
[ilmath]\eq a^2+b^2\ (\ +0j\ )[/ilmath]
[ilmath]\eq\vert a+bj\vert^2[/ilmath] - as required
• If [ilmath]a+bj[/ilmath] is the complex representation of [ilmath]\lambda[/ilmath] then we see [ilmath]\lambda\overline{\lambda}\eq\vert\lambda\vert^2[/ilmath]
2. Let [ilmath]a+bj\in\mathbb{C} [/ilmath], then:
• [ilmath](a+bj)+\overline{(a+bj)}\eq (a+bj)+(a-bj)\eq 2a[/ilmath]
• Thus if [ilmath]a+bj[/ilmath] is the complex representation of [ilmath]\lambda\ip{y,x} [/ilmath] then
• [ilmath]\overline{\lambda\ip{y,x} }+\lambda\ip{y,x}\eq 2\text{Re}(\lambda\ip{y,x})[/ilmath]
3. From [ilmath]e^{-j\theta}e^{j\theta}\eq e^{j\theta-j\theta}\eq e^0[/ilmath]
4. As for [ilmath]a+bj\in\mathbb{C} [/ilmath] we see:
• [ilmath]\vert a+bj\vert:\eq \sqrt{a^2+b^2} [/ilmath] and
• [ilmath]\vert \overline{a+bj}\vert\eq\vert a-bj\vert\eq\vert a+(-b)j\vert:\eq \sqrt{a^2+(-b)^2}\eq\sqrt{a^2+b^2}\eq\vert a+bj\vert[/ilmath] as required